2022
DOI: 10.1146/annurev-fluid-022421-011319
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Aggregation of Convective Storms

Abstract: Idealized simulations of the tropical atmosphere have predicted that clouds can spontaneously clump together in space, despite perfectly homogeneous settings. This phenomenon has been called self-aggregation, and it results in a state where a moist cloudy region with intense deep convective storms is surrounded by extremely dry subsiding air devoid of deep clouds. We review here the main findings from theoretical work and idealized models of this phenomenon, highlighting the physical processes believed to play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 107 publications
(132 reference statements)
1
45
1
Order By: Relevance
“…Convective self‐aggregation (CSA) refers to the spatial separation into deep convective and dry subregions occurring spontaneously in numerical simulations with homogeneous boundary and initial conditions (Bretherton et al., 2005 ; Held et al., 1993 ; Muller et al., 2022 ; Tompkins & Craig, 1998 ; Wing et al., 2017 ). CSA serves as a plausible mechanism for observed large‐scale tropical convective clustering, including the Madden‐Julian oscillation (Zhang, 2005 ) or the formation of tropical cyclones (Emanuel, 2018 ; Muller & Romps, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Convective self‐aggregation (CSA) refers to the spatial separation into deep convective and dry subregions occurring spontaneously in numerical simulations with homogeneous boundary and initial conditions (Bretherton et al., 2005 ; Held et al., 1993 ; Muller et al., 2022 ; Tompkins & Craig, 1998 ; Wing et al., 2017 ). CSA serves as a plausible mechanism for observed large‐scale tropical convective clustering, including the Madden‐Julian oscillation (Zhang, 2005 ) or the formation of tropical cyclones (Emanuel, 2018 ; Muller & Romps, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that sub-hectometer horizontal resolution or improved SFS models may be required to adequately represent shallow convective self-aggregation. They also call for a thorough analysis of the degree to which self-aggregation-which slows down appreciably as our model resolution increases-matters in nature, a question which has remained elusive for studies of their deep-convective counterparts (Muller et al, 2022). A good start in this direction is offered by simulations of the EUREC 4 A field campaign (Narenpitak et al, 2021;Saffin et al, 2022), which exhibit circulation-driven moisture aggregation in more realistic settings, and which compare favorably to the campaign's observations.…”
Section: Discussionmentioning
confidence: 99%
“…Many mechanisms have been proposed to explain this, including the collision and convective triggering of horizontally expanding and colliding cold pools of evaporated precipitation (Böing, 2016;Haerter, 2019;Tompkins, 2001) and gravity wave-convection interactions (Yang, 2021). Yet, perhaps the strongest consensus is on the importance of shallow circulations (Muller et al, 2022;Shamekh et al, 2020), configured to transport moisture from dry to moist columns.These circulations can be traced to differential, radiative cooling between moist regions, which trap outgoing longwave radiation in their moisture-rich lower atmosphere and under high clouds, and dry regions, which more readily radiate their thermal energy to space (Muller & Held, 2012). Such heating anomalies give rise to ascent in moist columns and descent in dry columns, and may be framed as a moisture-radiation instability (Beucler & Cronin, 2016;Emanuel et al, 2014) with negative moist gross stability (Bretherton et al, 2005;Raymond et al, 2009).…”
mentioning
confidence: 99%
“…Recent work has suggested that cold pools, when more properly resolved, can help in-hibit convective self-aggregation (Jeevanjee & Romps, 2013;Nissen & Haerter, 2021;Muller et al, 2022), but may conversely strengthen clustering under diurnal cycle conditions (Haerter et al, 2020;Jensen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%